Implementasi Corporate Sosial Responsibility Pada PT. Eloda Mitra Palembang - Dedi Handoko; Niken Ayuningrum; Yesita Astarina; Ferdyan Wana Saputra (LP2M Politeknik Jambi, 2023)
This study aims to provide an overview of the implementation of Corporate Social Responsibility and find out the CSR implementation efforts implemented by PT Eloda Mitra Palembang. The type of research used is qualitative descriptive research, this study seeks to describe the implementation of CSR as a form of business ethics related to the social responsibility of a company. Sampling was carried out using purposive sampling method, where the respondents interviewed were employees of PT Eloda Mitra Palembang, as well as questionnaires and in-depth interviews with operational managers of PT Eloda Mitra Palembang. The results of the study show that the CSR carried out by PT Eloda Mitra Palembang for the community and the environment in the aspect of education is in the form of buildings, educational facilities and subsidies. Improve health by building puskesmas in villages, providing equipment, deploying health workers as well as vehicles to provide health services to surrounding villages. Vocational training as well as efforts to develop businesses, provide support for SME initiatives and financing. For employees, the implementation of CSR programs aims to improve employee welfare, provide services, and training opportunities